Internal sources of ideas for innovation :a social network perspective (2018)
The dissertation explores the shared space that lies between innovation and social network research. The traditional perspective of innovation (Schumpeter, 1934) claims that different sources of ideas or knowledge are required to provide diversity that increases the chances to obtain innovations (Flemming, 2001). The relationship between the diversity of sources of ideas and innovation exists at different organizational levels of analysis and for alternative measures of innovative outcomes, such as patents, new products, or new knowledge in general. At the level of the firm, the more diverse the ideas used in the innovation process, the higher the likelihood to obtain new products or patents (Leiponen and Helfat, 2010; Phelps, 2010). At the individual level, the availability of non-redundant contacts increases the ability of individuals to generate ideas evaluated as valuable (Burt, 2004). Additionally, research has proven that specific properties of social networks facilitate the access to diverse information for different kinds of innovation (Phelps, Heidl, and Wadhwa, 2012). Different to other approaches that link a social network concept to an innovative outcome, the thesis seeks to join both fields into a single perspective. Usually, researchers perceive social networks as a set of tools and ignore the potential of networks to improve our theoretical thinking. The dissertation sequentially explored the intersection of innovation and social networks fields by asking first where the firms search for ideas to innovate; then, which changing social networks could be an essential source of ideas and, finally, by aiming at bridging both fields into a single view of innovation with a social network perspective